Bmi-1 promotes the proliferation, migration and invasion, and inhibits cell apoptosis of human retinoblastoma cells via RKIP - Qian Li; Te Fu; Ning Wei; Qiaoling Wang; Xin Zhang (Scientific Reports)
Abstract Retinoblastoma is one of the most common ocular malignancies in children. Bmi-1, a member of the Polycomb group family of transcriptional repressors, is expressed in a variety of tumors. The purpose of our study was to explore the role of Bmi-1 in retinoblastoma. RT-qPCR and western blot were used for calculating the mRNA and protein levels of Bmi-1 and RKIP. MTT, Wound healing and Transwell assays were performed to measure the proliferation, migration and invasion in retinoblastoma cells. Cell apoptosis was detected by flow cytometry. The volume and mass of transplanted tumors were detected in nude mice. Bmi-1 was over expressed, and RKIP was low expressed in retinoblastoma cells. Bmi-1 promoted cell proliferation, migration and invasion and suppressed cell apoptosis of Y79 and SO-RB50 cells. Downregulation of Bmi-1 and overexpression of RKIP inhibited cell proliferation, migration and invasion, and increased cell apoptosis. The functions of Bmi-1 knockdown on retinoblastoma cells were blocked by RKIP knockdown, but promoted by RKIP. Down-regulated Bmi-1 inhibited xenograft tumor growth, and RKIP exacerbated this inhibitory effect. Bmi-1 served as a potential therapeutic target for improving the efficacy of clinical treatment in retinoblastoma. All the findings revealed the functions of Bmi-1/RKIP axis in retinoblastoma tumorigenesis.